Arl13b regulates breast cancer cell migration and invasion by controlling integrin-mediated signaling - Casalou, Cristina (2019)
This work was supported by PhD fellowships from Fundação para a Ciência e a Tecnologia(FCT) to A. Faustino, A. Ferreira and P.C. (PD/BD/105898/2014, PD/BD/135506/2018 and PD/BD/128339/2017, respectively), a post-doctoral fellowship from FCT to C.C. (SFRH/BPD/78561/2011), the FCT Investigator Program to D.C.B. (IF/00501/2014/CP1252/CT0001), and grants from FCT (PTDC/BIM-MEC/4905/2014) and iNOVA4Health - UID/Multi/04462/2013, a program financially supported by FCT/ Ministério da Educação e Ciência, through national funds and co-funded by FEDER under the PT2020 Partnership Agreement.